Technological Aspects of Lithium-Titanium Ferrite Synthesis by Electron-Beam Heating - Lysenko E. N. Elena Nikolaevna; Vlasov V. A. Vitaliy Anatolievich; Nikolaev E. V. Evgeny Vladimirovich; Surzhikov A. P. Anatoly Petrovich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (2023, 2023)
Title screen